Isomerization and Dimerization of Indocyanine Green and a Related Heptamethine Dye. Issue 30 (22nd July 2019) - Rüttger, Franziska; Mindt, Sonani; Golz, Christopher; Alcarazo, Manuel; John, Michael
Abstract : Indocyanine green (ICG) and a second heptamethine cyanine dye were studied in detail using 2D NMR spectroscopy at multiple temperatures. In addition to the all‐ trans conformation, we found in both cases a small percentage of a specific β‐γ cis isomer. Exchange rates extrapolated from 2D EXSY spectra under slow exchange conditions are in agreement with that estimated from methine 1 H linewidths near coalescence and with previous photo‐isomerization studies. We could also confirm our previous hypothesis that, under aerobic conditions in combination with exposure to daylight, ICG undergoes radical dimerization specifically at the γ position. Abstract : Look at it in a different light! Cyanines undergo trans‐cis photo‐isomerization and light‐triggered oxidative dimerization. NMR spectroscopy was used to shed light on the structure of the photoisomers and dimers of two cyanine dyes.